The Implementation of Educational Supervision in Improving Teacher Professional Competence - armizawati, armizawati; Asmendri, Asmendri (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2022)
The implementation of educational supervision to enhance the teacher professionalism at MAS Thawalib Tanjung Limau, Tanah Datar Regency becomes  the main focus of this study. This study is a part of descriptive qualitative research. The head of the MAS, however, is the main source of research data. Observations and interviews are used as data collection techniques. The supervision provided by the head of MAS Thawalib Tanjung Limau plays a significant role as the effort to increase the quality of teachers. For increasing resource capacity and revamping materials to meet national education goals, strategies such as instructional supervision are helpful. The preparation stage, class observation, and assessment or feedback discussion are the three stages that make up this clinical supervision. Limited infrastructure and resources, lack of teacher discipline, and lack of teacher knowledge about efficient classroom management techniques are challenges experienced in the clinical supervision and teaching. This study shows that the principal's educational supervision places a vital position to support appropriate infrastructure and facilities of schools, maximize the teacher disciplinary action, and offer proper direction, and advice on efficient classroom management procedures.